2010
DOI: 10.1007/s10457-010-9313-z
|View full text |Cite
|
Sign up to set email alerts
|

Relating growth and nutrition to site factors in young chestnut plantations established on agricultural and forest land in northern Spain

Abstract: The growth and nutritional status of 97 hybrid chestnut plantations on former agricultural land and forest land were studied in relation to site conditions (climatic variables and soil properties). A single family of curves was obtained for classifying the early height growth of hybrid and sweet chestnut. Soil limitations and nutrient deficiencies were evident in the former forest land, whereas the agricultural soils were found to be generally suitable for growing chestnut. The stands with highest growth rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Forest nutrition management is an important factor in the management of wood forests since the rates of production are limited by the supply of one or more nutrients in almost all forests, a mixture of species, each with different nutrient requirements and nutrient cycling properties and efficiency of nutrient use (Khanna, 1997;Binkley and Ryan, 1998;Rouhi-Moghaddam et al, 2008;Álvarez-Álvarez et al, 2010). This way, high rates of production depend strongly on nutrient supply, efficiency of nutrient use, and, thus, on species selection.…”
Section: Introductionmentioning
confidence: 99%
“…Forest nutrition management is an important factor in the management of wood forests since the rates of production are limited by the supply of one or more nutrients in almost all forests, a mixture of species, each with different nutrient requirements and nutrient cycling properties and efficiency of nutrient use (Khanna, 1997;Binkley and Ryan, 1998;Rouhi-Moghaddam et al, 2008;Álvarez-Álvarez et al, 2010). This way, high rates of production depend strongly on nutrient supply, efficiency of nutrient use, and, thus, on species selection.…”
Section: Introductionmentioning
confidence: 99%
“…Although the general trend conflicts with findings by Evans (1986) of little fertiliser response in commercial chestnut coppices at Kings Wood, the soil medium in that case was relatively fertile loamy-clay plateau drift, unlike the growth medium used in this experiment. The contrast here is analogous to the superior growth of chestnut plantations on exagricultural, rather than forest soils described by Alvarez-Alvarez et al (2010).…”
Section: Treatment Responsesmentioning
confidence: 50%
“…In former agricultural soils, Alvarez-Alvarez et al (2010) found superior yields of plantations of Castanea sativa and the hybrid C. × coudercii where deeper profiles and the sup-plies of available phosphorus, Ca and K were greater than in forest soils. Laroche et al (1997) believed that calcium, an important element stabilising the middle lamella of cell walls, might be implicated in chestnut ring shake.…”
Section: Introductionmentioning
confidence: 94%
“…Physiographic and environmental strata profiling have been used in Spain [20,22] and Portugal [34] for digital mapping of the suitability of chestnut stands and the selection of stands to be studied. In this work, physiographic profiles of altitude and slope were the main distinctive characteristics of the current and potential expansion areas of chestnut stands, because of the aforementioned similitude of climate and soil type mosaic in the whole Marvão productive area.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, although adult chestnut stands withhold severe drought conditions, young trees are considered as far more sensitive to water stress. Thus, coppicing by allowing to obtain higher soil water and nutrient amounts, can enhance plant growing when water scarcity is not very drastic [21,22]. Chestnut prefers sedimentary or siliceous soils with acidic to neutral conditions, tending to occupy hills and ridges because their roots tend to decay in poorly drained soils.…”
Section: Introductionmentioning
confidence: 99%